Analysis of Consultant Building Project Management Using the CPM (Critical Path Method) - Kadang, Tandi; Hidayah, Puji Wahyu; Simarmata, Kamelia; Putri, Nathasya A.; Krisvinus, Krisvinus (Journal of Business Management and Economic Development, 2024)
Critical Path Method (CPM) is a technique used to plan and organize project schedules by identifying the critical path which is one of the most contributing aspects to project success. This research aims to formulate the completion time of the consultant office building construction project using the CPM method. Data collection techniques in this study were carried out through various activities, including field observations, interviews, and literature studies. The results showed that the application of CPM in project planning and scheduling can determine the critical path and identify the shortest duration for project completion. CPM enabled the acceleration of project completion from 592 days to 469 days, saving 123 days. This study confirms that the quality of project planning and control significantly affects the successful completion of the project. The findings support the use of CPM for time efficiency improvement on similar construction projects and recommend further research on the application of CPM on various other types of projects.